2021
DOI: 10.1002/jcsm.12849
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic supplementation attenuates age‐related sarcopenia via the gut–muscle axis in SAMP8 mice

Abstract: Background Age-related muscle dysfunctions are common disorders resulting in poor quality of life in the elderly. Probiotic supplementation is a potential strategy for preventing age-related sarcopenia as evidence suggests that probiotics can enhance muscle function via the gut-muscle axis. However, the effects and mechanisms of probiotics in age-related sarcopenia are currently unknown. In this study, we examined the effects of Lactobacillus casei Shirota (LcS), a probiotic previously reported to improve musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 41 publications
3
41
0
Order By: Relevance
“…The analysis was performed following the description of a previous study. 15 Differences in abundance were examined by the MetaStat method with adjustments for multiple comparisons.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis was performed following the description of a previous study. 15 Differences in abundance were examined by the MetaStat method with adjustments for multiple comparisons.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the gut microbiota was reported to employ SCFAs to benefit the host through several signaling pathways associated with the gut–brain 14 and gut–muscle axes. 15…”
Section: Introductionmentioning
confidence: 99%
“…It also reduced age related increases in inflammation by down regulating the proinflammatory cytokine TNF- α and upregulating the anti-inflammatory cytokine IL-10. In contrast to the fall in SCFAs usually seen in aging, Lactobacillus casei Shirota helped to maintain the butyrate levels in the aged mice ( 61 ). This study involved a small case series of six non-agenarian older adults (mean age: 90.8 ± 5.4 years) with sarcopenia who were administered the prebiotic 1-kestose (10 g/day for 2 weeks), there was an increase in the intestinal Bifidobacterium longum population along with increased skeletal muscle mass index and reduced body fat percentage ( 62 ).…”
Section: Other Forms Of Interventions Involving the Gut Microbiomementioning
confidence: 99%
“…131 Chen et al showed that the Lactobacillus casei supplementation in elderly mice could produce anti-ROS and anti-inflammatory effects as well as maintain muscle and mitochondrial functions. 132 The mechanism of intestinal microbiota on mitochondria is shown in Figure 1. Although the underlying mechanism needs to be studied further, the existing research evidence shows that the metabolites of intestinal microbiota, especially short-chain fatty acids (SCFA), are key intermediates affecting the gut-muscle axis.…”
Section: Intestinal Microbiotamentioning
confidence: 99%
“…138 FFAR3 is mainly expressed in adipose tissue and is related to obesity and other metabolic diseases. 132 GPR41 and GPR43, the main receptors of acetate, are expressed in almost all metabolically active tissues of the human body. Therefore, acetate may be one of the most important metabolites of the interaction between intestinal microbiota and host metabolites.…”
Section: Scfamentioning
confidence: 99%